Ansofaxine hydrochloride inhibits tumor growth and enhances Anti-TNFR2 in murine colon cancer model - Jing, Qianyu; Wan, Quan; Nie, Yujie; Luo, Junqian; Zhang, Xiangyan; Zhu, Lan; Gui, Huan; Li, Linzhao; Wang, Chenglv; Chen, Shuanghui; Wang, Mengjiao; Yuan, Haohua; et al. (Frontiers in Pharmacology, 2023)
As psychoneuroimmunology flourishes, there is growing concern about the impact of depression in cancer treatment. Currently, immunotherapy is believed to be the most promising way to completely cure cancer. However, most people fail to benefit from clinically approved immunotherapies. Tumor necrosis factor receptor 2 (TNFR2) antagonistic antibodies (Anti-TNFR2) targeting tumor-infiltrating regulatory T cells (Tregs) has achieved great results in preclinical studies, and with a favorable toxicity profile than existing immunotherapies, and is expected to become a new generation of more effective treatment strategies. There is compelling evidence that depression suppresses the anti-tumor immune response, promotes the progression of cancer, and inhibits the effectiveness of cancer immunotherapy. Recent studies have reported that antidepressants can not only alleviate the depressant condition of cancer patients, but also strengthen the anti-tumor immunity, thus suppressing tumors. Therefore, understanding the effects of combination therapy with antidepressants and immunotherapy may help design new strategies for cancer immunotherapy. The results show that, as expected, oral antidepression, ansofaxine hydrochloride, enhanced peripheral dopamine levels, promoted CD8 + T cell proliferation, promoted intratumoral infiltration of M1 and NK cells, decreased the proportion of tumorinfiltrating exhausted CD8 + T cells, and strengthened anti-tumor immunity, thereby inhibiting colon cancer growth.In combination therapy, oral administration of ansofaxine hydrochloride enhanced the efficacy of Anti-TNFR2, and produced long-term tumor control in with syngeneic colorectal tumor-bearing mice, which was attributable to the reduction in tumor-infiltrating Treg quantity and the recovery of CD8 + T cells function. Our work presents additional experimental evidence for the development of Anti-TNFR2 to treat colon cancer, while providing a possible strategy for treating colon cancer patients with depression.